Pengaruh Likuiditas, Pertumbuhan Penjualan, dan Risiko Bisnis Terhadap Nilai Perusahaan - Dewi, Ida Ayu Puspita Trisna; Sujana, I Ketut (E-Jurnal Akuntansi, 2019)
This study aims to analyze the effect of Liquidity, Sales Growth, and Business Risk to Company Value (study on Telecommunication Company listed on Indonesia Stock Exchange period 2011-2016). The study population includes all telecommunication companies listed on Indonesia Stock Exchange period 2011-2016. The research population data are 30 companies with observation samples of 5 companies. The method used in this research is purposive sampling method. Data analysis was tested by using multiple linear regression analysis. The results of this study indicate that liquidity has a positive effect on corporate value, sales growth positively affect the value of the company and business risk negatively affect the value of the company. Keywords: liquidity, sales growth, business risk and corporate value